Case report: Cyclosporine A-induced extrapyramidal syndrome following hematopoietic stem cell transplantation - Al-Amrani, Fatema; Al Rawas, Abdulhakeem; Al-Ajmi, Eiman; Al Futaisi, Amna (Frontiers in Neurology, 2023)
Introduction Cyclosporine A-associated neurotoxicity has been reported in up to 40% of patients and its wide range of neurological adverse effects have been reported, ranging from mild tremors to fatal leukoencephalopathy. Extrapyramidal (EP) neurotoxicity is a rare manifestation of cyclosporine. Cyclosporine-induced extrapyramidal syndrome remains a rare adverse reaction. Design/methods A database search was performed for studies in patients from all age groups. We found a total of 10 articles reporting EP as an adverse effect of cyclosporine A. A total of 16 patients were found, and a thorough review of these patients was performed. A comparison of patients was performed to highlight common clinical presentations, investigations during the symptomatic phase, and prognosis. In addition, we describe an 8-year-old boy who developed cyclosporine-related extrapyramidal signs on day 60 post-hematopoietic stem cell transplantation for beta-thalassemia. Conclusion Cyclosporine A can induce neurotoxicity resulting in diverse symptoms. Signs of EP are rare manifestations of cyclosporine neurotoxicity and should be considered when evaluating post-transplant recipients of cyclosporine when they are present with any EP symptoms. Discontinuation of cyclosporine results in good recovery in most patients.